Development of Curriculum Management Model Based on Multicultural Character in Pesantren Khalafiyah - Retno Ekaningrum, Ifada; Widodo, Joko; Wasino, Wasino; Sugiyo, Sugiyo (The Journal of Educational Development, 2018)
This article is a result of research on the development of multicultural character-based curriculum management model in the Islamic Boarding School (henceforth: Pesantren) Khalafiyah. The education pattern in Pesantren  Khalafiyah is a boarding school pattern. Pesantren khalafiyah is unique compared to other school types. The schools curriculum is an integrative one that combines the formal school curriculum and the pesantren curriculum. In addition, because learning patterns incorporate habituation to form multicultural characters, the curriculum development model is typically relevant to the typology of Pesantren Khalafiyah. This research was conducted at Pesantren Khalafiyah Assalam Kudus and Pesantren Muhammadiyah Kudus. The data were analyzed using the  Research and Development approach. This study aimed to develop multicultural character-based curriculum management models and procedures. The results show that the boarding school-based Pesantren Khalafiyah has special features seen from the school governance, specialty outputs, curriculum loads, and evaluative models of learning. In addition to applying the formal school curriculum, Pesantren Khalafiyah also applies non-formal charges and hidden curriculum. The cost incurred in this type of school is the overlapping between subjects - the number of subjects is more than that in regular schools - and the evaluation model of learning. The provided solution to the problems of the boarding school requires the development of integrative curriculum, which combines the madrasah, pesantren, and habituation curriculum. The integrative curriculum development design contains curriculum formulation procedures by integrating the formal school curricula with the non-formal curricula (pesantren), including the preliminary evaluation procedures.